2015
DOI: 10.5603/ep.a2016.0023
|View full text |Cite
|
Sign up to set email alerts
|

The effects of fat distribution and some adipokines on insulin resistance

Abstract: Introduction: The risk of developing insulin resistance and metabolic syndrome is particularly high in central obesity. In this study we evaluated the effects of fat distribution and some adipokines on insulin resistance in prediabetic patients. Material and methods: Eighty-seven age-and sex-matched patients were divided into three groups according to their 75-gram oral glucose tolerance test results as follows: impaired fasting glucose group, impaired glucose tolerance group, and normal glucose tolerance grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 23 publications
(29 reference statements)
0
17
0
1
Order By: Relevance
“…The interplay of pro-inflammatory and metabolic disturbances is pivotal in for developing insulin resistance and its ensuing morbidities (Bilir et al, 2016). DIO is associated with increased inflammatory markers (Hosseinzadeh-Attar et al, 2016) and perturbations of adipose secretory hormones (adiponectin, visfatin, resistin, and leptin) (Trayhurn and Beattie, 2001; Simons et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The interplay of pro-inflammatory and metabolic disturbances is pivotal in for developing insulin resistance and its ensuing morbidities (Bilir et al, 2016). DIO is associated with increased inflammatory markers (Hosseinzadeh-Attar et al, 2016) and perturbations of adipose secretory hormones (adiponectin, visfatin, resistin, and leptin) (Trayhurn and Beattie, 2001; Simons et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The anti-inflammatory adipocytokine adiponectin has been found to be closely associated with insulin resistance and cardiovascular disease [4][5][6][7]. Recent studies have suggested that the suppression of inflammation and upregulation of adiponectin may attenuate metabolic syndrome and insulin resistance [5,7].…”
Section: Introductionmentioning
confidence: 99%
“…This supports our study. Insulin resistance was also observed in prediabetic patients, which increased in parallel to waist circumference [25]. Pancreatic beta cell function as revealed by Matsuda index was significantly lower in mice of group T as compared to mice of group C by one month and worsened by five months of feeding.…”
Section: Discussionmentioning
confidence: 89%